Pengaruh Penyuluhan Kesehatan Metode BEFAST Terhadap Peningkatan Pengetahuan Deteksi Dini Tanda Gejala Stroke - Apriyati; Huzaifah, Zaqyyah; Retno Wulan, Diah (LPPM Universitas Sari Mulia, 2024)
Background: Stroke is one of the major health problems; early recognition of stroke signs and symptoms plays a crucial role and is a key factor in its management. Counseling on the BEFAST method (Balance Loss, Eyesight Change, Facial Movement, Arm Movement, Speech, Time) is necessary to enhance public awareness of early stroke detection. Objective: This study aimed to determine the effect of health counseling using the BEFAST method on increasing knowledge of early detection of stroke signs and symptoms among hypertensive patients. Method: The study employed a pre-experimental design with a one-group pretest and posttest approach. The population consisted of hypertensive patients treated at Puskesmas Simpang Empat 2, with a total sample of 64 individuals selected using purposive sampling. Data analysis was performed using the Wilcoxon signed rank test. Result: Before counseling, most respondents had moderate knowledge of early stroke detection (64.2%, 43 respondents). After counseling, the majority of respondents demonstrated improved knowledge in the good category (94%, 63 respondents). The analysis showed a significant effect of the BEFAST method on increasing knowledge of early stroke detection (ρ = 0.000). Conclusion: These findings suggest that the BEFAST method can be used as an effective approach in health education to improve public awareness of early stroke signs and symptoms.